Effects of breastfeeding on the risk factors for metabolic syndrome in preterm infants. (28th August 2014) - Ikeda, N.; Shoji, H.; Murano, Y.; Mori, M.; Matsunaga, N.; Suganuma, H.; Ikeno, M.; Hisata, K.; Hirayama, S.; Ueno, T.; Miida, T.; Shimizu, T.
<x content-type="archive" xml:space="preserve">Abstract</x> Evidence suggests that breastfeeding during infancy lowers the risk of metabolic syndrome (MS) and its attendant risk factors in adult life. To investigate the influence of feeding type on the risk factors of MS, we assessed insulin sensitivity and lipid and apolipoprotein metabolism in preterm infants. Blood samples were collected from preterm infants at the time of discharge. Infants were separated into two groups: a breast milk (BM) group receiving ⩾90% of their intake from BM, and a mixed-fed (MF) group receiving ⩾50% of their intake from formula. The following indices were then compared between the two groups. Blood glucose and serum insulin levels were used to calculate the quantitative insulin sensitivity check index (QUICKI). We also measured serum total cholesterol (TC), low-density lipoprotein cholesterol (LDLc), high-density lipoprotein cholesterol (HDLc), apolipoprotein-A1 (apoA1) and apolipoprotein-B (apoB) levels, and the ratios of TC/HDLc, LDLc/HDLc and apoB/apoA1. The mean gestational age was 32.9 weeks at birth, and blood samples were collected at a mean corrected age of 37.4 weeks. There were 22 infants in the BM group and 19 in the MF group. QUICKI was significantly higher in the BM group. TC, HDLc and apoA1 were not significantly different between the groups, but LDLc and apoB levels were significantly higher in the BM group. The TC/HDLc, LDLc/HDLc and apoB/apoA1 ratios were significantly higher in the BM group. In preterm infants, the type of feeding exposure in the early postnatal period may influence glucose, lipid and apolipoprotein metabolism, and affect markers of MS.